42‐1: Development of Cu BCE‐Structure IGZO TFT for a High‐ppi 31‐in. 8K × 4K GOA LCD. Issue 1 (2nd June 2017) - Ge, Shi-Min; Li, Shan; Chen, Shu-Jhih; Kong, Xiang-Yong; Meng, Yan-Hong; Shi, Wen; Shi, Long-Qiang; Wu, Wei; Liu, X; Gan, Qi-Ming; Zhao, Yang; Zhang, CK; et al.
Abstract : The electrical characteristics of the BCE‐structure IGZO TFTs were studied. Through modifying the passivation layer and optimizing the selection of copper acid and PFA material, the TFTs exhibited good threshold voltage and reliability. Finally, a high performance 31‐inch 8K4K GOA LCD was demonstrated.